'Dites un mot et daignez nous tendre la main': The Emergence of Hugo's Lost Feminist Voice from His Oratory in Exile. (1st October 2016) - Ní Riordáin, Jeanna
Abstract : The silence of oblivion which plagued Hugo throughout his lifetime was never more keenly felt than during his exile. However, it was this fear of nothingness which gave potent urgency to Hugo's public discourse and to his role as a spokesperson for les misérables . During his exile Hugo's voice also reached a distinct, though much less documented group of disfavoured people, namely the female victims of revolution, and leading French and international feminists. Through his eulogies to women like Louise Julien and George Sand, and his extensive epistolary correspondences with women, Hugo became a prominent figure in the feminist struggle both in France and throughout the world in the mid- nineteenth century. His woefully neglected public discourse on women's rights from this time reveals his support for such defining demands in nineteenth-century feminism as women's rights to universal suffrage, equal citizenship, and the participation of women in the future French republic.